Insights into the natural history of Ampullariids from the Lower Río de la Plata Basin, Argentina - Martín, Pablo Rafael (2013)
Apple snails (Ampullariidae) are renowned globally as successful invaders, as voracious pests of aquatic crops and as promoters of ecosystem changes in natural wetlands.